Tangerine - Bloor, Edward, 1950- (Orlando, Fla. : Harcourt, 2006)
Twelve-year-old Paul, who lives in the shadow of his football hero brother Erik, fights for the right to play soccer despite his near blindness and slowly begins to remember the incident that damaged his eyesight.
Notable/Best Books (A.L.A.)
School Library Journal
Wilson's Junior High School
Young Adult
Young Adult
Keywords: Brothers -- Fiction; Diaries -- Fiction; People with disabilities -- Fiction; People with visual disabilities -- Fiction; Soccer -- Fiction; Brothers -- Fiction; Diaries -- Fiction; People with physical disabilities -- Fiction; Soccer -- Fiction; Visually handicapped -- Fiction; Florida -- Fiction; Florida -- Fiction